2010
DOI: 10.1017/s0023879100009377
|View full text |Cite
|
Sign up to set email alerts
|

The Color of Child Mortality in Brazil, 1950–2000: Social Progress and Persistent Racial Inequality

Abstract: Now that racism has been officially recognized in Brazil, and some universities have adopted affirmative-action admission policies, measures of the magnitude of racial inequality and analyses that identify the factors associated with changes in racial disparities over time assume particular relevance to the conduct of public debate. This study uses census data from 1950 to 2000 to estimate the probability of death in the early years of life, a robust indicator of the standard of living among the white and Afro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…We used the variable 'ethnicity' in two ways: (1) for descriptive analysis in its original form, using the categories of the national survey, including white, black, asian, multiethnic, or indigenous; and (2) for the models, we recategorized it into 'white' and 'non-white'. The latter category (i.e., non-white) included black, asian, multiethnic, and indigenous groups to create a group that potentially combines similar experiences of oppression based on race, as described in Wood et al 19 (source: 10.1017/S0023879100009377) and Skidmore 20 (source: 10.1017/S0022216X00004703). The IBGE survey measured food insecurity according to the reduced eight item version of the Brazilian Food Insecurity Scale (EBIA), the official Brazilian tool to determine food insecurity levels in the population.…”
Section: Methodsmentioning
confidence: 99%
“…We used the variable 'ethnicity' in two ways: (1) for descriptive analysis in its original form, using the categories of the national survey, including white, black, asian, multiethnic, or indigenous; and (2) for the models, we recategorized it into 'white' and 'non-white'. The latter category (i.e., non-white) included black, asian, multiethnic, and indigenous groups to create a group that potentially combines similar experiences of oppression based on race, as described in Wood et al 19 (source: 10.1017/S0023879100009377) and Skidmore 20 (source: 10.1017/S0022216X00004703). The IBGE survey measured food insecurity according to the reduced eight item version of the Brazilian Food Insecurity Scale (EBIA), the official Brazilian tool to determine food insecurity levels in the population.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 In Brazil, extreme inequality is driven by class, gender, and race or ethnicity, 5 and ethnoracial inequalities in child survival have been documented between 1950 and 2000. 13,14 No nationally representative study of ethnoracial inequalities in child survival has been identified after this period. This analysis aimed to examine childhood mortality rates according to maternal race or skin colour in a recent 6-year follow-up of a cohort of more than 19 million Brazilian children, in an effort to inform political decisions and public health interventions to reduce ethnoracial inequality in child health.…”
Section: Introductionmentioning
confidence: 99%